The Description of Medical Check-up Results of the Oil and Gas Workers at PT. X in East Kalimantan in 2022-2023: Gambaran Hasil Medical Check-up pada Pekerja Minyak dan Gas Bumi PT. X di Kalimantan Timur Tahun 2022-2023 - Muhammad Abdul Aziz Hafidhuddin; Duma, Krispinus; Tresnasari, Putri (ITKES Wiyata Husada Samarinda, 2026)
The benefits of medical check-up in the mining sector have been proven in improving workers’wellbeing. Medical check-up not only identifies potential health problems with unidentifiable symptoms, but also provides prevention or treatment services to reduce the number of deaths related to health conditions. This research aims to provide a description of medical check-up results of the oil and gas workers at PT. X in East Kalimantan. It is expected that the results of this research can provide deep understanding related to the health conditions of the workers in the work environment of oil and gas. This research applied quantitative method with descriptive observational design. The data of this research were taken from the medical check-up results carried out by the oil and gas workers at PT. X in East Kalimantan in 2022-2023. This approach aimed to give an accurate description of the worker health conditions in the work environment, especially in oil and gas industry. The research findings revealed an increase number of workers with an increasing participation of women, a change in age distribution, and an increasing number of health problems, including an increase in diabetes, obesity, and a shift in the health status of workers.